Magnesian Basalts of Shiveluch Andesite Volcano, Kamchatka - Volynets O.N.; Ponomareva V.V.; Babansky A.D. (1997)
The eruptive history of the Shiveluch andesite volcano included two Holocene events, during which the volcano erupted unusual rocks: medium-potassium, amphibole-bearing magnesian basalts (7600 years ago) and high-potassium magnesian basalts with phlogopite and amphibole (3600 years ago). The volumes of tephra were approximately 0.1 and 0.3 km3, respectively. Some of the mineralogical and geochemical features of the Holocene basalts were inherited by the subsequent basaltic andesites and andesites. These are similar in Mg variation ranges of olivine, clinopyroxene, and amphibole phenocrysts, high Mg contents, and high Cr and Ni concentrations. This and the results of mass-balance calculations do not contradict the view that the Shiveluch volcanic rocks originated during the crystal fractionation of Holocene basalt melts. However, the other geochemical features of the Shiveluch rocks, e.g., their similar REE contents, cast doubt on the formation of the magnesian basaltic andesites through fractional crystallization of magnesian basalt magma and suggest that they originated as a result of interaction between magnesian basalt magma and a depleted mantle material at a shallow depth. At the same time, the different mineral compositions of the Holocene medium- and high-potassium basalts and the results of mass-balance calculations indicate that their parental magmas might be produced by the melting of different rocks.